Emphysematous cystitis treated with targeted antibiotic therapies: a report of two cases - Quanbo Yu; Yanhui Wang; Xinqi Zhang (Frontiers in Medicine, 2026)
Emphysematous cystitis (EC) is a rare, complicated urinary tract infection characterized by gas formation in and around the bladder wall, often occurring in older adults with diabetes mellitus, urinary tract obstruction, or long-term indwelling urinary catheters. EC can be easily misdiagnosed due to atypical symptoms and signs. Delayed treatment causes life-threatening complications like emphysematous pyelonephritis, bladder perforation, or septic shock. Here, we retrospectively analyzed two cases of EC who had been effectively treated and discharged following antibiotics, strict blood sugar control, bladder irrigation, and symptomatic and supportive treatment. Through literature review, we summarized the clinical characteristics, diagnostic skills, and therapeutic strategies for EC. Our experience may inform the early diagnosis and standardized management to improve the prognosis of EC.